Community Structure and Dispersion Patterns of Macrophytes and Macrozoobenthos in the Intertidal Ecosystem of the Eastern Pananjung Nature Reserve - Agustiana, Muhamad Agung Triyudha; Aulia Safira, Nadya; Savhira Noor, Najmy; Noor Fitriansyah, Muhammad (Jurnal Biologi Tropis, 2025)
The intertidal ecosystem of the Pananjung Nature Reserve plays a vital role yet remains vulnerable to environmental pressures and anthropogenic activities. This study aims to analyze the community structure and distribution patterns of macrophytes, as well as their association with macrozoobenthos, on the eastern side of the Pananjung Nature Reserve. The research was conducted using a purposive sampling method employing line transects and quadrat plots. Inventory results recorded low macrophyte diversity (6 species), significantly dominated by the seagrass Enhalus acoroides and the macroalgae Padina australis. Conversely, the macrozoobenthos community exhibited high diversity with 26 species identified, wherein Charonia tritonis (Gastropoda) was the most dominant species. Distribution pattern analysis indicated that the majority of macrophytes were clumped, except for E. acoroides, which exhibited a uniform distribution pattern. This study concludes that E. acoroides functions as an ecosystem engineer; although the vegetation habitat is classified as simple (Margalef Index 0.53), the morphology and distributional stability of this species create complex microhabitats that support high macrozoobenthos diversity (Margalef Index 5.34). These findings emphasize the urgency of protecting key vegetation species to maintain the trophic balance of coastal ecosystems.